Plasma-catalytic reforming of liquid hydrocarbons - Nedybaliuk, O.A.; Chernyak, V.Ya.; Kolgan, V.V.; Iukhymenko, V.V.; Solomenko, O.V.; Fedirchyk, I.I.; Martysh, E.V.; Demchina, V.P.; Klochok, N.V.; Dragnev, S.V. (Вопросы атомной науки и техники, 2015)
The series of experiments studying the plasma-catalytic reforming of liquid hydrocarbons was carried out. The dynamic plasma-liquid system based on a low-power rotating gliding arc with solid electrodes was used for the investigation of liquid hydrocarbons reforming process. Conversion was done via partial oxidation. A part of oxidant flow was activated by the discharge. Synthesis-gas composition was analysed by means of mass-spectrometry and gas-chromatography. A standard boiler, which operates on natural gas and LPG, was used for the burning of synthesis-gas. Проведена серия экспериментов, изучающих плазменно-каталитическое реформирование жидких углеводородов. Динамическая плазменно-жидкостная система на основе маломощной вращательной скользящей дуги с твердыми электродами использовалась для исследования процесса реформирования жидких углеводородов. Конверсия была реализована путем частичного окисления. Часть потока окислителя активировали разрядом. Состав синтез-газа анализировался с помощью масс-спектрометрии и газовой хроматографии. Стандартный котел, который работает на природном и сжиженном газе, был использован для сжигания синтез-газа. Проведено серію експериментів, які вивчають плазмово-каталітичне реформування рідких вуглеводнів. Для дослідження процесу реформування рідких вуглеводнів використовувалася динамічна плазмово-рідинна система з обертальною ковзною дугою малої потужності з твердими електродами. Конверсія була реалізована шляхом часткового окислення. Частину потоку окисника активували розрядом. Склад синтез-газу аналізувався за допомогою мас-спектрометрії та газової хроматографії. Для спалювання синтез-газу був використаний стандартний котел, який працює на природному та зрідженому газі.